Sosialisasi Pelaksanaan Pengelolaan Obat Di Puskesmas Mamajang - Aripa, Lusyana; Betan, Abu Bakar; Zaenal, Zaenal; Wahyuni, Sri; Utami, Yuri Pratiwi; Imrawati, Imrawati (Asosiasi Guru dan Dosen Seluruh Indonesia, 2023)
Drug management is a pharmaceutical service activity that starts from planning, procurement, distribution, use and disposal of drugs. The aim is to ensure the continuity and availability of efficient, effective and rational medicines, increase the competency of pharmaceutical staff, create a management information system and implement service quality control and implementation relationships in drug management at the Mamajang Community Health Center, Mamajang District, Makassar City. Collection was carried out through in-depth interview techniques and direct observation. The results of drug planning at the Mamajang Community Health Center are in accordance with the drug management guidelines which are seen based on needs at the Community Health Center. Requests for drugs are in accordance with the procedures for procuring/requesting drugs from the Health Service via LPLPO to the District Pharmacy Warehouse (GFK). The distribution of medicines at the Mamajang Community Health Center is not in accordance with the drug management guidelines from GFK and is not in accordance with the needs at the Community Health Center, due to the lack of budget from the APBD which is channeled through the City Health Service. The conclusion is that the planning and use of drugs is in accordance with procedures, while the distribution of drugs is not in accordance with drug management guidelines because the APBD budget is not channeled through the Health Service. So it is hoped that when distributing medicines from the Makassar City Health Service or (GFK) they should pay attention to the procurement/request for medicines based on the LPLPO. The high population ratio in Pamenang, Tanjung, and Gangga Districts compared to existing health facilities and personnel is a very principal problem related to health education for the community, including information about health. One of them is about the correct procedures for obtaining, using, storing and managing medicines which includes how to use special medicines. The aim of this socialization is to educate human resources at the Mamajang Community Health Center. Socialization of this program is carried out through the delivery of material, discussions, questions and answers, demonstrations by pharmacists. The participants happened to be human resources at the Community Health Center who were very enthusiastic about this program because of the participants' activeness in asking and answering questions about drug management.